Relationships between adrenarcheal hormones, hippocampal volumes and depressive symptoms in children. (June 2019) - Ellis, Rachel; Fernandes, Anna; Simmons, Julian G.; Mundy, Lisa; Patton, George; Allen, Nicholas B.; Whittle, Sarah
Highlights: Low levels of testosterone associated with higher depressive symptoms in boys. High levels of DHEA predict larger hippocampal volumes in boys and girls. High testosterone related to depressive symptoms via hippocampal volume in girls. Results suggest timing of adrenarche important for depression vulnerability. Abstract: Early timing of puberty (i.e., advanced pubertal maturation relative to same-age peers) has been associated with depressive symptoms during adolescence. To date, research on this relationship has focused on gonadarche, the second phase of puberty, while less is known about the first phase of puberty, adrenarche. Increasing evidence suggests that androgens that rise during adrenarche, most notably dehydroepiandrosterone (DHEA) and testosterone, may be involved both in the development of the hippocampus, and risk for depression. The current study investigated whether hippocampal volumes mediated the relationship between adrenarcheal timing (based on relative levels of adrenarcheal hormones) and depressive symptoms in children. Data were collected from a cross-sectional sample of 88 children (46 female) selected to have relatively increased variance in these androgens. Participants completed brain MRI structural scans, provided saliva samples for hormones, and completed the Children's Depression Inventory (CDI). Contrary to predictions, larger right hippocampi significantly partially mediated the positive relationship between early timing of testosterone exposure (i.e., relatively high levels of testosterone for one's age) and depressive symptoms in girls. No other evidence of significant mediation effects was obtained, however DHEA and testosterone exposure showed unique effects on hippocampal volumes in males and females, and larger hippocampal volumes predicted higher depressive symptoms in the entire sample. These results suggest that adrenarcheal timing may be related to hippocampal development and depressive symptoms, extending current knowledge of pubertal risk processes.